The Influence of SOP and Training on Work Productivity with Supervision as a Moderating Variable - Putra, Wahyudi; Nuryanti, Nuryanti; Novrianti, Dian Puspita (CV. Rayyan Dwi Bharata, 2023)
This research was conducted at Perum Jamkrindo Pekanbaru Branch. The purpose of this study was to find out whether Standard Operating Procedures (SOP) and Training affect Work Productivity and whether Supervision is able to moderate the relationship between Standard Operating Procedures (SOP) and Training on Work Productivity at Perum Jamkrindo Pekanbaru Branch. The population in this study were all employees of Perum Jamkrindo Pekanbaru Branch, totaling 42 people. The sampling method used total sampling, namely as many as 42 respondents. The results of this study are (1) There is a significant influence between Standard Operating Procedures (SOP) on Productivity, (2) There is a significant effect between Training on Productivity, (3) Supervision is able to moderate the relationship between Standard Operating Procedures (SOP) on Productivity, (4) ) Supervision is not a moderating variable in the relationship between training and work productivity.